A Remarkable Stone Implement resembling a Knife found at Caisteal nan Gillean, Oronsay - Grieve, Symington (Proceedings of the Society of Antiquaries of Scotland, 1922)
A knife-shaped stone implement was found in a shell midden along with fish bones and scale, charcoal and fire-cracked stones. It is suggested that it functioned as a scraper, and was used to remove cooked fish skins.